A life cycle assessment of oxymethylene ether synthesis from biomass-derived syngas as a diesel additive. (1st November 2017) - Mahbub, Nafisa; Oyedun, Adetoyese Olajire; Kumar, Amit; Oestreich, Dorian; Arnold, Ulrich; Sauer, Jörg
Abstract: The life cycle energy consumption and greenhouse gas (GHG) emission performances of forest biomass-derived oxymethylene ether (OME) synthesis used as a diesel additive are analyzed in this study. OME, a new alternative liquid fuel, has great miscibility with conventional fuels like diesel. OME can reduce combustion emissions significantly when used as a diesel additive without any modification to the engine. A data-intensive spreadsheet-based life cycle assessment (LCA) model was developed for OME synthesis from woodchips derived from two different kinds of forest biomass, whole tree and forest residue. Woodchip harvesting, chip transportation, chemical synthesis of OME from biomass-derived syngas, OME transportation to blending, and vehicle combustion of this transportation fuel were considered in the system boundary. The results show that the whole tree pathway produces 27 g CO2 eq/MJ of OME, whereas the forest residue pathway produces 18 g CO2 eq/MJ of OME over 20 years of plant life. The difference is mainly due to some emissions-intensive operations involved in biomass harvesting and biomass transportation such as skidding, road construction, etc., in the whole tree pathway. Also, vehicle combustion was found to be the most GHG-intensive unit for both pathways. OME combustion in a vehicle accounts for about 77% and 83% of the total life cycle GHG emissions for the whole tree and forest residue pathways, respectively. This study also compares the diesel life cycle emission numbers with the life cycle emissions of OME derived from forest biomass, and it was observed that GHG emissions can be reduced by 20–21% and soot (black carbon) emissions can be reduced by 30% using a 10% OME blended diesel as a transportation fuel compared with conventional diesel. Highlights: Study analyzed GHG emissions of oxymethylene ether (OME) as a diesel additive. Two types of forest biomass are considered in our model to produce OME. Vehicle combustion is the most energy-intensive unit. OME-blended diesel reduces GHG and soot emissions significantly.